Evaluation of Diclofenac by UV-Vis Spectrophotometer in Some Locally Produced Tablets - Hasan, MK; Hossain, MA; Sultana, A; Shoeb, M; Nahar, N (Dhaka University Journal of Science, 2017)
Diclofenac is a common and randomly used pharmaceutical product, was evaluated for its active ingredient by UV-Vis spectrophotometer at 282 nm. Diclofenac sodium of 50 mg dose of seven different companies of Bangladesh was extracted from the tablets, cleaned up and the active ingredient was evaluated. Evaluation was carried out with respect to calibration curve of standard diclofenac sodium. Amount of diclofenac in 50 mg tablets of seven different companies were found to be in the range of 47.91 ± 0.90 to 58.52 ± 0.41 mg. Recovery experiments were done by spiking excipient of the medicine at two different concentration levels with 5-7 replicate studies. Correlation coefficient (r2) was found to be 0.9974 and the recovery was103.39 ± 3.93 to 107.96 ± 3.56 % for the drug. Dhaka Univ. J. Sci. 65(2): 163-165, 2017 (July)